Operational analysis of bus lanes on arterials application and refinement. - St. Jacques, Kevin R.; Levinson, Herbert S.; United States. Federal Transit Administration; Transit Cooperative Research Program; National Research Council (U.S.). Transportation Research Board; Wilbur Smith and Associates ([Washington, D.C.] Transportation Research Board, National Research Council, 2000)
"This TCRP digest provides the results of TCRP Project A-7A, "Field evaluation of bus lanes on arterials," conducted by Kevin R. St. Jacques, of Wilbur Smith Associates, in association with Herbert S. Levinson, Transportation Consultant."
Caption title.
"Sponsored by the Federal Transit Administration."
September 2000.
Includes bibliographical references (p. 50).
Keywords: Bus lanes -- United States -- Evaluation; Highway capacity -- United States; Traffic flow -- United States